(3GdeLehY GdePgH aj bhGYO GdePgHs - (3Ndjd Hf cjcdOj Hf YHO Gddg GdYdGFj GdOeTbqj, CHh SYjO, UdGM GdOjf , J (B761 (3g`s ((3YHO GdQMef Hf YeQ GdJQePi GdCTYQi GdTGaYi s)
(3ChdgG (B:s
(3jHJOF HaUd (B" (3hceG NQL GdYHO hGdeHYV Yf HbjI Gdecdajf (B" s
(3GdfSNI HgG MhGTs
(3efbhdI ef fSNI efbhdI ef NW GdeDdas
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs